Chromospheric Jets and Their Properties - Ehsan Tavabi; Sima Zeighami (Iranian Journal of Astronomy and Astrophysics)
In this study we review solar chromospheric jets and characteristics of them. The chromosphere and transition region are the interface between the solar photosphere and the corona, which plays a key role in the formation and acceleration of the solar wind. In recent years, scientists have made great efforts to understand the mechanism of energy transfer in the solar chromosphere and corona. The researchers suggest that the key to solving this problem may lie in understanding the nature of the small-scale transient events that are distributed across the surface of the Sun. Of these, solar spicules are the most prominent small-scale dynamical phenomena in the chromospheric regions that drive relatively cold material from the lower chromosphere to the corona. Spicules can heat the corona both by ejecting hot plasma and by energy transfer by magnetohydrodynamic (MHD) waves. These dynamical structures are formed when photospheric oscillations and convective flow along the magnetic field lines penetrate into the chromosphere.